Kedudukan Hukum Tangkapan Layar Percakapan Melalui Aplikasi WhatsApp sebagai Perluasan Alat Bukti Tulisan dalam Perkara Wanprestasi: Analisis Putusan Nomor 258/Pdt.G/2023/PN Blb (Perspektif Hukum Acara Perdata) - Lily Sujatmiko; Nabilla Zumarnis; Berliana Cahya Fatimah; Sri Handayani (Pusat Riset dan Inovasi Nasional, 2026)
Evidence is a fundamental element in the legal proof process that serves as the basis for judges to examine, assess, and decide cases in court. Along with the advancement of information technology, the form of evidence has evolved, including digital evidence such as screenshots of conversations through digital communication applications like WhatsApp. This study aims to analyze the legal position and evidentiary value of digital conversation screenshots within the Indonesian legal system. The research method uses a normative juridical approach by examining laws and regulations, legal doctrines, and relevant court decisions. The results indicate that screenshots of conversations have legal recognition as electronic evidence; however, their evidentiary strength is limited and requires support from other forms of evidence. Judges apply the principle of Unus Testis Nullus Testis, meaning that screenshots cannot stand alone as sole evidence and must be supported by additional legal proof to fulfill the requirements of valid, complete, and convincing legal evidence.